Remittance Trends 2006 - Mohapatra, Sanket (World Bank, Washington, DC, 2012)
In nominal dollar terms Latin America and the Caribbean region remains the largest recipient of (recorded) remittances 2006. However, as a share of gross domestic product (GDP) remittances are highest in the Middle East and North Africa region. Due to a lack of data, remittance flows to Sub-Saharan Africa are grossly underestimated. Recorded remittance flows have grown robustly in virtually every region, although most quickly in Europe and Central Asia and in East Asia and the Pacific. The doubling of recorded remittances over the past five years is a result of: (a) increased scrutiny of flows since the terrorist attacks of September 2001; (b) reduction in remittance costs and expanding networks in the remittance industry; (c) the depreciation of the U.S. dollar (which raises the value of remittances denominated in other currencies); and (d) growth in the migrant stock and incomes. Although the United States remains the largest single source of remittances, many remittance-receiving developing countries also have a significant number of migrants in countries in the Euro area. Since remittances receipts in developing countries are typically measured in US dollars, movement in the Euro-dollar exchange rates can have a significant valuation effects on remittance, even without accounting for the wealth effect when the Euro appreciates or depreciates in real terms relative to the dollar.